2016
DOI: 10.1007/s11356-016-7003-8
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of using fungi as bioresource for bioremediation of pesticides in the environment: a critical review

Abstract: Pesticides are used for controlling the development of various pests in agricultural crops worldwide. Despite their agricultural benefits, pesticides are often considered a serious threat to the environment because of their persistent nature and the anomalies they create. Hence removal of such pesticides from the environment is a topic of interest for the researchers nowadays. During the recent years, use of biological resources to degrade or remove pesticides has emerged as a powerful tool for their in situ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(56 citation statements)
references
References 181 publications
0
56
0
Order By: Relevance
“…A summary of environmental contaminants as laccase substrates from published research in the year 2016 is provided in Table 3. The contaminants investigated include dyestuffs (Singh R. L. et al, 2015; Sen et al, 2016), polycyclic aromatic hydrocarbons (PAHs) (Librando and Pappalardo, 2013), endocrine disrupters (Cabana et al, 2007; Husain and Qayyum, 2012; Gasser et al, 2014), and pesticides (Maqbool et al, 2016). …”
Section: Laccase Applications In Biodegradation Of Ppcpsmentioning
confidence: 99%
“…A summary of environmental contaminants as laccase substrates from published research in the year 2016 is provided in Table 3. The contaminants investigated include dyestuffs (Singh R. L. et al, 2015; Sen et al, 2016), polycyclic aromatic hydrocarbons (PAHs) (Librando and Pappalardo, 2013), endocrine disrupters (Cabana et al, 2007; Husain and Qayyum, 2012; Gasser et al, 2014), and pesticides (Maqbool et al, 2016). …”
Section: Laccase Applications In Biodegradation Of Ppcpsmentioning
confidence: 99%
“…However, the extracellular peroxidase enzyme of this fungus is non-specific and has been associated with degradation of xenobiotics like chlorocyclohexane and chlorobenzene (Diez 2010; Meuser 2013). Saprophytic fungi like Aspergillus and Pencillum have been reported to degrade chlorocyclohexane (Maqbool et al 2016). Besides, Trametes, Aspergillus and Penicillium have been reported for their ability to degrade dioxin (Chang 2008; Deshmukh et al 2016; Pathak and Navneet 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies it was observed that fungus played a significant role in reducing organic compound levels through enzymes they produce or mycelial adsorption (38), (39), (40), (41). Thus, it was decided to study the degradation and adsorption performed by strain T23.…”
Section: Methodsmentioning
confidence: 99%